2021
DOI: 10.35974/acuity.v6i2.2482
|View full text |Cite
|
Sign up to set email alerts
|

The Important Role of Extensive Reading Strategy in Indonesian EFL Learning Contexts

Abstract: Abstract   Academic literacy is one of the paramount global competencies that should be mastered by worldwide university academicians including Indonesian EFL learners. To fully fulfill this holistic educational objectivity, extensive reading plays a key role in fostering overarching Indonesian EFL learners’ target language proficiency due to the inducement of pleasurable, continual, and stress-free L2 reading learning dynamics proffered by this student-centered learning approach. Furthermore, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Literature from global studies show that extensive reading leads to gains in different language skills and has a positive impact on the learners' reading fluency, vocabulary knowledge and reading interest (Wijaya, 2021& Suk, 2017. Allington and McGill-Franzen (2021) show that research published since 2000 shows that evidence is more clear that reading volume plays a role in reading development.…”
Section: English Foreign Language In Tanzaniamentioning
confidence: 99%
See 1 more Smart Citation
“…Literature from global studies show that extensive reading leads to gains in different language skills and has a positive impact on the learners' reading fluency, vocabulary knowledge and reading interest (Wijaya, 2021& Suk, 2017. Allington and McGill-Franzen (2021) show that research published since 2000 shows that evidence is more clear that reading volume plays a role in reading development.…”
Section: English Foreign Language In Tanzaniamentioning
confidence: 99%
“…Previous studies on EFL extensive reading conducted elsewhere have used different methods such as a one-group pretest-posttest design (Singkum & Chinwonno, 2021). Whereas Wijaya (2021) used a document analysis approach to yield renewable insights concerning extensive reading strategy.…”
Section: Extensive Reading For English Language Learningmentioning
confidence: 99%
“…It implies that students read based on their interest. Extensive reading provides students with maximum exposure to read text attracting their interest [19]. They just want to read what they want to, regardless their major of study.…”
Section: Students' Reading Themesmentioning
confidence: 99%
“…Extensive reading is one of the activities implemented for students to get them used to read. The extensive reading implementation may significantly impact English as a foreign language (EFL) learners' target language skills, learning moods, attitudes, and involvement [5]. Some previous studies revealed the positive impact of extensive reading programs on students' English proficiency.…”
Section: Introductionmentioning
confidence: 99%